Analisis Upaya Guru dalam Mengatasi Kesulitan Belajar Membaca Siswa - Saugadi Saugadi; Agung Rinaldy Malik; Burhan Burhan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This research aims to find out how teachers try to overcome learning difficulties reading grade 1 students of SDN Sandana, Galang Tolitoli District. This research uses a qualitative approach with a descriptive method. The subjects of this study were first grade teachers and first graders. The data collection in this study is using interviews and documentation. The data analysis techniques used data collection, data reduction, data presentation and conclusion drawing. Based on the results of the study can be concluded that the teacher's efforts in overcoming the difficulty of learning to read grade 1 students are providing additional lessons, providing homework and providing motivation to learn to read. Keywords : Teacher, Learning Difficulties Reading, Students.